5G and EMF Exposure: Misinformation, Open Questions, and Potential Solutions - Elzanaty, Ahmed; Chiaraviglio, Luca; Alouini, Mohamed-Slim (Frontiers in Communications and Networks, 2021)
The massive deployment of advanced wireless networks is essential to support broadband connectivity, low latency communication, and Internet of Things (IoT) applications. Nevertheless, in the time of coronavirus disease (COVID-19) there is a massive amount of misinformation and uncertainty about the impact of fifth-generation cellular network (5G) networks on human health. In this paper, we investigate the main categories of misinformation regarding 5G, i.e., fake theories, the misconception of 5G features, and open questions that require further research. Then, we propose two novel approaches for the design of ElectroMagnetic Field (EMF)-aware cellular networks that can reduce human exposure to radiofrequency radiation.